2016
DOI: 10.1557/mre.2016.2
|View full text |Cite
|
Sign up to set email alerts
|

Status and challenge of Mg battery cathode

Abstract: Current performance of Mg battery cathode is reviewed. Perspective for research in this fi eld is provided and discussed.Mg battery has recently gathered more and more interest as a high energy density replacement of current Li-ion battery. Signifi cant progress has been made in developing sustainable anode and novel electrolyte. However, the success of Mg battery still high demands the search of cathode material with high energy density, good rate capability, and nice cyclability. This current review focuses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 83 publications
0
22
0
Order By: Relevance
“…However, low-operation voltage (1.2 V) and capacity (theoretically 120 mAh g −1 ) limit the energy density of Chevrel phase to at most ~20% of typical LIB cathode such as LiCoO2 (Aubach et al, 2000). A crucial hurdle toward the development of practical rMB is therefore to find suitable cathodes meeting the requirements of energy density, cyclability, and rate capability Mohtadi and Mizuno, 2014;Muldoon et al, 2014;Bucur et al, 2015;Huie et al, 2015;Song et al, 2016;Zhang and Ling, 2016a).…”
mentioning
confidence: 99%
“…However, low-operation voltage (1.2 V) and capacity (theoretically 120 mAh g −1 ) limit the energy density of Chevrel phase to at most ~20% of typical LIB cathode such as LiCoO2 (Aubach et al, 2000). A crucial hurdle toward the development of practical rMB is therefore to find suitable cathodes meeting the requirements of energy density, cyclability, and rate capability Mohtadi and Mizuno, 2014;Muldoon et al, 2014;Bucur et al, 2015;Huie et al, 2015;Song et al, 2016;Zhang and Ling, 2016a).…”
mentioning
confidence: 99%
“…As can be seen, the input power and the heat output of the three different heat pumps are different for the different variants. In order to compare their operating performance, the experimental heating efficiency e exp is defined using equation (18), the attenuation rate m of the heating efficiency is defined using equation (19) and the comparison rate u is defined using equation (20), as follows: Fig. 7.…”
Section: Resultsmentioning
confidence: 99%
“…Heo et al measured and analyzed the effects of flash tank vapor injection on the heating performance of a two-stage heat pump with an inverterdriven twin rotary compressor for different frequencies [17]. Zhang et al established an experimental set up of economized vapor injection air-source heat pump (EVI-ASHP) system in cold regions of China, and showed that the air-source heat pump with the EVI technique could improve the thermal performance by 4-6% with respect to that without EVI [18]. Cho et al measured the cooling and heating performances of R410A and R32 multi-heat pumps with a sub-cooled vapor injection (SCVI) and found that the R410A and R32 multi-heat pumps with vapor injection showed 2.1-6.3% higher cooling capacity than those without vapor injection [19].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] In this context, multivalent metal ion (Mg, Zn, Al) batteries can be a better choice due to their high abundance, low cost and high volumetric capacity. [8][9][10][11][12][13][14][15] Amongst the recently developed batteries, Al batteries have garnered interest due to the higher abundance (third most abundant metal in earth's crust), high gravimetric (3 A h g À1 ) and volumetric capacity (8.04 A h cm À3 ) compared to other metal ions. [12][13][14][15] However, these merits are due to the anodic part and there is an essential need to look out for materials to improve the cathodic part, which can provide suitable electrochemical properties.…”
Section: Introductionmentioning
confidence: 99%